Formulasi Body Scrub dari Ampas Kopi dan Rimpang Temulawak (Curcuma Xanthorhiza Roxb) - Sari, Yetti Puspita (Journal of Beauty and Cosmetology (JBC), 2020)
Body scrub functions to lift bodys rough and dull skin cells. Coffee grounds with a coarse texture that contains scrub grains and antioxidant in large quantities can be used as a body scrub. This study aimed to determine the effect of the proportion of coffee grounds and curcuma on physical characteristics including aroma, color, time duration to remove scrubs, changes of the skin after being rubbed with the scrub product, the skin moisture, shelf life (microbiological test), and panelist preferences. This study used experimental research design. The independent variable was the proportion of coffee grounds and curcuma (2:3), (3:2), and (4:1). The dependent variables included aroma, color, time duration to remove scrubs, changes of the skin after being rubbed with the scrub product, the skin moisture, shelf life (microbiological test), and panelist preferences. Data were collected using observation performed by 50 panelists. The obtained data were analyzed using ANOVA and Duncan's test carried out using SPSS. Results showed that there was an effect of the proportion of coffee grounds and curcuma on the physical characteristics. The aroma produced jasmine smell, light yellowish black color, a change in skin color after using the scrub product, the skin became moister. The X2 sample was the best proportion of the body scrub favored by the panelists. In accordance with the microbiology test, X2 sample had a shelf life of more than 7 days with the amount of bacterial and fungal contamination below.